Efficient generation of influenza virus with a mouse RNA polymerase I-driven all-in-one plasmid - Zhang, Xiangmin; Curtiss, Roy (Virology journal, 2015)
The current influenza vaccines are effective against seasonal influenza, but cannot be manufactured in a timely manner for a sudden pandemic or to be cost-effective to immunize huge flocks of birds. We propose a novel influenza vaccine composing a bacterial carrier and a plasmid cargo. In the immunized subjects, the bacterial carrier invades and releases its cargo into host cells where the plasmid expresses viral RNAs and proteins for reconstitution of attenuated influenza virus. Here we aimed to construct a mouse PolI-driven plasmid for efficient production of influenza virus. A plasmid was constructed to express all influenza viral RNAs and proteins. This all-in-one plasmid resulted in 10(5)-10(6) 50% tissue culture infective dose (TCID50)/mL of influenza A virus in baby hamster kidney (BHK-21) cells on the third day post-transfection, and also reconstituted influenza virus in Madin-Darby canine kidney (MDCK) and Chinese hamster ovary (CHO) cells. A 6-unit plasmid was constructed by deleting the HA and NA cassettes from the all-in-one plasmid. Cotransfection of BHK-21 cells with the 6-unit plasmid and the two other plasmids encoding the HA or NA genes resulted in influenza virus titers similar to those produced by the 1-plasmid method. An all-in-one plasmid and a 3-plasmid murine PolI-driven reverse genetics systems were developed, and efficiently reconstituted influenza virus in BHK-21 cells. The all-in-one plasmid may serve as a tool to determine the factors inhibiting virus generation from a large size plasmid. In addition, we recommend a simple and robust "1 + 2" approach to generate influenza vaccine seed virus.